Endemicity of Urinary Schistosomasis in Ogbese-Ekiti Community of Ise-Orun Local Government Area of Ekiti State, Nigeria: Endemicity of Urinary Schistosomasis (Biological Sciences - PJSIR, 2009)
In random examination of 191 students of Ogbese-Ekiti community of Nigeria for urinary schistosomasis, 170 (89%) were found positive for Schistosoma haematobium eggs in their urine. The prevalence in the secondary school was 97.4%, while the prevalence in the primary school was 87.5%. The overall mean intensity of S. haematobium eggs/10 ml of urine in this community was 339.4. Also, 5.9% of the infected pupils excreted above 1000 eggs/10 ml of urine, while 59.8% had moderate intensity (50-499 eggs/10 ml of urine). The perentage macrohaematuria was 84. Among five aquatic snails Bulinus (B) forskalii, Bulinus (B) globosus, Pila ovata, Potadoma moerchi and Melanoides tuberculata of river Ogbese, only B. (P) globosus shed the characteristics cercariae of S. haematobium. A monthly mean of B. globosus in river Ogbese was 53.2 and an increase in the population density of the snail occurred between November and May, 2004. The highest infection rate of B. (P) globosus with S. haematobium occurred in the month of March.